2020
DOI: 10.26832/24566632.2020.0503019
|View full text |Cite
|
Sign up to set email alerts
|

Availability of aqua drugs and their uses in semi intensive culture farms at Patuakhali district in Bangladesh

Abstract: A survey was undertaken to examine the accessibility of aqua-drugs and their applications in the semi-intensive aquaculture farms in Patuakhali district. A total of 83 stakeholders were selected and data gathered from aqua-medicine stores, representatives of different pharmaceuticals and semi-intensive aqua-farms owners via questionnaire interviews. PRA tools like focused group discussion, cross-checking, and key informant interviews were also used. Results show that 78% of farmers conduct polyculture and rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…A total of 15 antibiotics were identified and farmers were reported with irresponsible and frequent use of such drugs without approval and without knowing their effects on fish health (Faruk et al, 2021). Several issues regarding improper use of aquatic medications, such as lack of information about chemical use, sufficient dosage, form of application, and indiscriminate use of antibiotics have been reported by Hasan et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 15 antibiotics were identified and farmers were reported with irresponsible and frequent use of such drugs without approval and without knowing their effects on fish health (Faruk et al, 2021). Several issues regarding improper use of aquatic medications, such as lack of information about chemical use, sufficient dosage, form of application, and indiscriminate use of antibiotics have been reported by Hasan et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…Total AMDC reported The literature from 2011 to 2020 reported 1484 names, types, and generics of AMDC from different part of Bangladesh. Among the literature, in 2020, the highest number of AMDC were reported (Das et al, 2020;Hasan et al, 2020;Ullah et al, 2020), followed the year 2017 (208 AMDC), 2014 (196 AMDC), 2019 (189 AMDC) and it is observed some reported AMDC in every year except 2013; due to lack of any published document in 2013, we did not find any AMDC in that year (Figure 5). The result of this analysis gives an understandable trend that, the farmer's preferences of AMDC is raising in a different part of the country.…”
Section: Area Wise Research Trends Of Amdc In the Last Decadementioning
confidence: 69%
“…In contrast to our study, studies in other countries such as China, Switzerland, and Poland showed that aac(6’)-lb-cr was the predominant PMQR gene in E . coli isolates from aquatic samples [ 34 , 54 56 ]. Further investigations of the isolates using a comparative genomic approach will provide more insights into the characteristics of isolates driving this discriminate distribution of PMQR genes.…”
Section: Discussionmentioning
confidence: 99%